2008
DOI: 10.1002/cpe.1291
|View full text |Cite
|
Sign up to set email alerts
|

Parallel processing of remotely sensed hyperspectral imagery: full‐pixel versus mixed‐pixel classification

Antonio J. Plaza

Abstract: SUMMARYThe rapid development of space and computer technologies allows for the possibility to store huge amounts of remotely sensed image data, collected using airborne and satellite instruments. In particular, NASA is continuously gathering high-dimensional image data with Earth observing hyperspectral sensors such as the Jet Propulsion Laboratory's airborne visible-infrared imaging spectrometer (AVIRIS), which measures reflected radiation in hundreds of narrow spectral bands at different wavelength channels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In those cases, important aspects such as the size of the spatial-domain partitions or the need to overlap adjacent partitions arise. These aspects have been addressed in the previous work [30,31].…”
Section: Hyperspectral Data Partitioningmentioning
confidence: 95%
“…In those cases, important aspects such as the size of the spatial-domain partitions or the need to overlap adjacent partitions arise. These aspects have been addressed in the previous work [30,31].…”
Section: Hyperspectral Data Partitioningmentioning
confidence: 95%
“…Increased experimentation, algorithm improvement, and validation over more urban areas of greater size must also be accompanied by increased research in advanced computing to support the data volume and complexity of hyperspectral algorithm advances, most of which are computationally intensive. For researchers interested in this significant challenge, the work of Plaza (2008, 2007), and Plaza et al. (2006) form an excellent starting point.…”
Section: Summary: Future Directionsmentioning
confidence: 99%
“…In the context of hyperspectral imaging applications, it has been demonstrated that the scalability of parallel algorithms is directly related to the size of the messages to be exchanged through the communication network of the system when the parallel algorithm is run [4], i.e. the latency for large message sizes (typical in hyperspectral imaging applications, since each pixel vector is made up of hundreds of spectral values) is extremely sensitive to the size of the message.…”
Section: Introductionmentioning
confidence: 99%